An Analysis of the Solvency Position of Scheduled Urban Co-Operative Banks in India - Jesudasan, Smita; Fernandes, Frenzia (SFIMAR Research Review, 2016)
Solvency is a term that refers to an enterprise's state of financial health. Solvency refers to an enterprise's capacity to meet its long-term financial commitments. A solvent company is one that owns more than it owes; in other words, it has a positive net worth and a manageable debt load. The essential aspect of the study is to analyse the solvency position of Scheduled Urban Cooperative Banks in the Indian industry despite the pressure of keen competition and monetary environment. Investors, debt holders and regulators are interested in the solvency analysis and overall financial profile of co-operative banks to understand how well their assets and managed and debt is serviced. The study considers 33 co-operative banks in India for the analysis of solvency position. Springate Model, Fulmer Model, Altman Z Score and Altman Z" Score are the research models considered to examine their solvency position. The results provide evidence that Bombay Mercantile Cooperative Bank Limited fails to meet the cut-off of all the solvency models and therefore is in a risky position, followed by Rajkot Nagrik Sahakari Bank Ltd., Janalaxmi Co-operative Bank Ltd. and Mapusa Urban Cooperative Bank of Goa Ltd.